Eichmann in Jerusalem: A Report on the Banality of Evil - Arendt, Hannah 1906-1975; Elon, Amos (New York Penguin Books, 2006)
Eichmann in Jerusalem: A Report on the Banality of Evil is a 1963 book by political thinker Hannah Arendt. Arendt, a Jew who fled Germany during Adolf Hitler's rise to power, reported on the trial of Adolf Eichmann, one of the major organizers of the Holocaust, for The New Yorker. A revised and enlarged edition was published in 1964. Arendt's subtitle famously introduced the phrase "the banality of evil". In part the phrase refers to Eichmann's deportment at the trial as the man displayed neither guilt for his actions nor hatred for those trying him, claiming he bore no responsibility because he was simply "doing his job" ("He did his ‘duty'...; he not only obeyed 'orders', he also obeyed the 'law'."p. 135).
Includes bibliographical references (p. [299]-303) and index.
Keywords: Eichmann, Adolf -- 1906-1962; Journalism; Holocaust; Crescendo; Law